Analisis Kesulitan Belajar Matematika Siswa Kelas XI MIPA SMA Negeri 2 Gunung Talang Kabupaten Solok - Stella Adri Yanti; Sefna Rismen; Lita Lovia (STKIP PGRI Sumatera Barat, 2022)
Difficulty in learning mathematics is a disorder in students that can lead to a lack of student success in learning. Difficulties can be in the form of difficulties in understanding concepts, principles and problem solving. The purpose of this study was to determine the form of students' learning difficulties in mathematics. This research method uses a qualitative descriptive approach. The subjects in this study were selected by purposive sampling and as research subjects were students of class XI MIPA 3 SMA Negeri 2 Gunung Talang. The research instruments were tests and interviews. The data analysis technique uses the Miles and Huberman technique, namely, data reduction, data presentation, and drawing conclusions. The results showed that students had difficulty applying the concept to the inability indicator in inferring information from a given concept. Difficulty in applying principles to indicators relating concepts between materials, difficulties in using formulas and difficulties in mastering algorithms. Difficulty in solving problems, on indicators of students' inability to perform calculations.